RNA Editing—Systemic Relevance and Clue to Disease Mechanisms? - Meier, Jochen C.; Kankowski, Svenja; Krestel, Heinz; Hetsch, Florian (Frontiers in Molecular Neuroscience, 2016)
Recent advances in sequencing technologies led to the identification of a plethora of different genes and several hundreds of amino acid recoding edited positions. Changes in editing rates of some of these positions were associated with diseases such as atherosclerosis, myopathy, epilepsy, major depression disorder, schizophrenia and other mood disorders as well as cancer and brain tumors. This review summarizes our current knowledge on that front and presents glycine receptor C-to-U RNA editing as a first example of disease-associated increased RNA editing that includes assessment of disease mechanisms of the corresponding gene product in an animal model.